2008
DOI: 10.1093/ndt/gfm919
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex in primary glomerulonephritis

Abstract: Women have a better outcome than men in MGN and FSGS but not in IgA nephropathy. These benefits are mostly mediated through both lower proteinuria and blood pressure at presentation and throughout follow-up, although females did have an independent advantage at higher levels of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 41 publications
6
97
0
4
Order By: Relevance
“…Although this is consistent with the literature, suggesting males have a worse renal survival (5,7), it is important to note that despite a lower percentage of males within this group, their rate of progression was not significantly different from the females. This is consistent with a recent analysis from our group, wherein we demonstrated that progression (slope of CrCl) is not dependent on sex in MGN except when urine protein persistently exceeds 8 g/d (22).…”
Section: Discussionsupporting
confidence: 93%
“…Although this is consistent with the literature, suggesting males have a worse renal survival (5,7), it is important to note that despite a lower percentage of males within this group, their rate of progression was not significantly different from the females. This is consistent with a recent analysis from our group, wherein we demonstrated that progression (slope of CrCl) is not dependent on sex in MGN except when urine protein persistently exceeds 8 g/d (22).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the multivariate Cox regression analysis shows that PLA 2 R-Ab levels together with men and older age are predictors for the increase in serum creatinine. Being a man has been discussed to be a predictor for an unfavorable outcome in patients with MN (16), and in our cohort, older patients had a 15% higher risk to reach the study end point per 5 years of age.…”
Section: Discussionmentioning
confidence: 57%
“…Age at onset,50 years, women, baseline proteinuria,8 g/d, and preserved renal function at presentation are predictors of SR (37,38). The genetic variants analyzed in this study showed no significant association with SR, although 18% of NSR patients exhibited either high (more than two) or low (less than two) FCGR3B CN compared with 4% of SR patients; this finding suggests that alterations in FCGR3B CN could hinder SR. FCGR3B CN was correlated with protein expression and immune complex clearance (39); therefore, changes in FCGR3B CN could alter the balance between Fc receptors, disrupting the tightly regulated immune system (20) and impeding achievement of SR.…”
Section: Discussionmentioning
confidence: 58%